Comparative Analysis of Pancreatic Biochemical Markers in Diabetes and Acute Pancreatitis ("Conference on Universal Science Research 2023", 2024)
The pancreas serves both exocrine and endocrine functions, playing a pivotal role in digestion and metabolism. Disruptions to its function can result in serious conditions, such as diabetes mellitus, which affects glucose metabolism, and acute pancreatitis, characterized by inflammation and necrosis of pancreatic tissue. Understanding the biochemical markers related to these diseases is essential for diagnosing, managing, and predicting outcomes, especially in severe cases of acute pancreatitis and complex diabetes